Features of planning of the studies of indoor air levels within the action plan implementation (Environment & Health, 2020)
Objective: Our aim was to substantiate the methodological aspects of the study of the radon hazard of the territories.Materials and methods: The measurements of the radon-222 levels were carried out with the help of the passive track radonometry method in the heating season. Cellulose nitrate film of LR-115 type was used as a detector. The time of the exposure of radon accumulators made up 1-2 months. After the chemical etching procedure, the detectors were counted for the number of damage tracks by the method of spark counting.To establish the registration efficiency of the track detectors (calibration), they were exposed in the radon atmosphere with a known radon activity. The radon atmosphere, patented by the Institute of Public Health, is a calibration source accredited by the National Body of Standardization and Accreditation of Ukraine.Results: Indoor radon-222 measurements were performed in more than 30 thousand buildings. The indoor radon-222 EEVA geometric mean for rural houses was found to be 52 Bq*m-3 (for gas radon, this value is 130 Bq*m-3), for apartments located on the ground floor of multi-storied buildings - 40 (100) Bq*m-3, above the ground floor - 23 (58) Bq*m-3 with a standard deviation of 62 (155) Bq*m-3, 48 (120) Bq*m-3 and 28 (70) Bq*m-3, correspondently.The national average level of the standard for radon-222 of 100 (250) Bq•m-3 was found to be exceeded in 19% of cases, the level of 200 (500) Bq*m-3 - in 5.7% of cases.Effective radiation doses for the population of the country have been determined. Non-radiation factors, affecting the effectiveness of studies, have been analyzed.The algorithm for the assessment of the radon risk degree for the territory has been developed. It includes the analysis of the structure of housing resources, determination of the most typical engineering-and-planning solutions for buildings, integral method of radon measurement, identification of the critical types of buildings based on the measurements of radon levels, calculation of radiation risks from radon for the population.The basic requirements for the primary radon monitoring in the context of the action plan implementation have been identified.
Keywords: indoor radon; effective dose; radiation risks; algorithm for actions